Pengaruh Bahasa Ibunda dan Identiti Budaya Terhadap Pembagunan Prasetia Keusahawanan dalam Kalangan Pelajar Institusi Pengajian Tinggi Awam di Malaysia - Mohd Senu, Awang (2024)
Entrepreneurial intention refers to the dimension of Entrepreneurial Intention that remains as a subject of continuous research interest due to its significant role in motivating individuals to embark on a career in entrepreneurship. A widely used and enduring model for measuring entrepreneurial intention is the Theory of Planned Behaviour (TPB). This mixed-method study aims to investigate the impact of the antecedent variables of the Theory of Planned Behaviour (TPB) model, reinforced by the incorporation of cultural identity as an independent variable. Furthermore, this study aims to assess the function of the mother language as an intermediary between the variables of the TPB model and cultural identity in influencing entrepreneurial intention. The study comprised a sample of 426 Malaysian IIUM students for quantitative analysis. Nine individuals who showed a pre-commitment to entrepreneurship were chosen as informants for qualitative enquiry. This explanatory research employed SPSS 26 software for pilot study and Smart PLS4 software to assess the research model's validity and reliability and perform numerical analysis. Using NVIVO 14, an artificial intelligence program, qualitative analysis was conducted. Research findings suggest that the concept of mother language has a statistically significant and positive impact on Attitude Towards Behaviour, as evidenced by a t-value of 3.278 and a p-value of 0.001, below the significance level of 0.05. The variable of Subjective Norm, via the mediation of the mother language, has a t-value of 3.033 and a p-value of 0.002, which is also below the significance level of 0.05. Perceived Behavioural Control, influenced by the mother language, has a t-value of 3.358 and a p-value of 0.001, which is less than the significance level of 0.05. Moreover, the mediation of Cultural Identity by the mother language yields a t-value of 4.651 and a p-value of 0.000, again below the significance level of 0.05. These values are classified as positive, acceptable, and statistically significant. The findings that the mother language significantly impacts entrepreneurial intention are further supported by the qualitative analysis conducted using NVIVO 14. Upon analysing the research results, the researchers concluded that the mother language substantially impacts the entrepreneurial intention and behaviour of students at Public Universities in Malaysia. The findings of this study can be employed by other scholars, policymakers, and stakeholders in the entrepreneurial ecosystem to foster the development of more environmentally independent future entrepreneurs.